Studies on standardization of organic production technology for Aloe (Aloe barbadensis) cultivation in semi-arid region (Indian Journal of Arid Horticulture, 2025)
This present study was conducted to standardize the nutrient requirement of plant through different organic sources for optimum growth and yield and quality of Aloe (Aloe barbadensis Mill.) plant during 2018-19 and 2019-20 at CCS HAU, Hisar for cultivation under arid and semi-arid conditions of Haryana. Results achieved during 2018-19, revealed that maximum plant height (59.70 cm), suckers per plant (4.50); numbers of leaves per plant (10.35) and leaf length (47.40 cm) were recorded in T5 (Vermicompost 7.5 t ha-1) which was significantly higher than treatments T1 (Control) and T6 (Neem cake 1.5 t ha-1). However, leaf yield and gel yield were found highest in T5 (36667 & 20449 kg ha-1, respectively) that was statistically superior with rest of treatments except T3 and T7. Likewise, the results achieved during 2019-20, revealed that maximum plant height (59.1 cm), suckers per plant (4.0), numbers of leaves per plant (10.80) and leaf length (57.6 cm) were registered with T5 which was significantly higher than treatments T1 and T6. However, leaf yield was found significantly higher with T5 (83117 kg/ha) that was statistically at par with T3 and T4. Gel yield was found significantly higher with T5 (43377 kg/ha) that was statistically at par with T3. Therefore, application of vermicompost 7.5 t ha-1 is recommended in aloe for commercial cultivation under arid and semi-arid region of Haryana.